2018
DOI: 10.1029/2018jc014195
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variability of pCO2, Carbon Fluxes, and Saturation State on the West Florida Shelf

Abstract: The West Florida Shelf (WFS) is a source of uncertainty for the Gulf of Mexico carbon budget.Data from the synthesis of approximately 135,000 pCO 2 values from 97 cruises from the WFS show that the shelf waters fluctuate between being a weak source to a weak sink of carbon. Overall, the shelf acts as a weak source of CO 2 at 0.32 ± 1.5 mol m À2 yr À1 . Subregions, however, reveal slightly different trends, where surface waters associated with 40-200-m isobath in the northern and southern WFS are generally weak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 51 publications
5
22
0
Order By: Relevance
“…The winters of 2010 and 2011 showed anomalous low SSTs for much of the North Atlantic, including the Caribbean (Buchan et al, 2013). Rivière and Drouard (2015) point out the contrasting phase of the NAO during 2010 and 2014. The negative NAO index in 2010 corresponds to low SST and low fCO 2w while maximum in the NAO in 2014 is associated with higher SSTs and fCO 2w .…”
Section: 1029/2019jc015366mentioning
confidence: 81%
“…The winters of 2010 and 2011 showed anomalous low SSTs for much of the North Atlantic, including the Caribbean (Buchan et al, 2013). Rivière and Drouard (2015) point out the contrasting phase of the NAO during 2010 and 2014. The negative NAO index in 2010 corresponds to low SST and low fCO 2w while maximum in the NAO in 2014 is associated with higher SSTs and fCO 2w .…”
Section: 1029/2019jc015366mentioning
confidence: 81%
“…A more recent estimate for the west Florida shelf is 4.4±18.0 g C m −2 yr −1 (Robbins et al, 2018). Huang et al (2015) estimated a larger uptake on the northern gulf shelf of 11 ± 44 g C m −2 yr −1 (i.e., about twice the estimate of Robbins et al, 2014) and reported a much larger uncertainty. In an analysis that combines satellite and in situ observations, Lohrenz et al (2018) estimated a similar uptake for the northern Gulf of Mexico of 13 ± 3.6 g C m −2 yr −1 .…”
Section: Gulf Of Mexicomentioning
confidence: 90%
“…Smaller shelf regions within the gulf differ markedly from this mean flux. The West Florida shelf and western gulf shelf act as sources to the atmosphere, with estimated annual average fluxes of 4.4 ± 1.3 and 2.2 ± 0.6 g C m −2 yr −1 , respectively; the northern gulf acts as a sink, with an estimated flux of 5.3 ± 4.4 g C m −2 yr −1 , and the Mexican shelf is almost neutral, with an estimated uptake flux of 1.1±0.6 g C m −2 yr −1 (Robbins et al, 2014). A more recent estimate for the west Florida shelf is 4.4±18.0 g C m −2 yr −1 (Robbins et al, 2018).…”
Section: Gulf Of Mexicomentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have 265 described to some degree surface pCO 2 seasonality within the GoM (e.g. Lohrenz et al, 2010;Robbins et al, 2018), but less has been done to describe seasonal patterns for other inorganic carbon system variables. In the present study, we focused our analysis on the seasonal cycles of surface pCO 2 and Ω Ar , but seasonal patterns of surface DIC and TA were also reported.…”
Section: Simulated Carbon Patternsmentioning
confidence: 99%